TELAAH KESYARIAHAN AKAD PADA KOPERASI (Studi di KPRI Universitas Brawijaya) - Asfi Manzilati; Munir, Misbakhul (Islamic Economics and finance in Focus, 2022)
The concept of business in Islam is controlled by halal and haram rules, which is a differentiator from conventional business. One form of business in Islam is Sharia Cooperatives with various sharia contract products. one of way to achieve its sharia, it is necesarry to study using its terms and conditions. It also needs supervision related to the sharia of the contract which is carried out by the Sharia Supervisory Board (DPS) from the internal cooperative itself. The existence of the Sharia Supervisory Board (DPS) has not been able to guarantee the sharia of the contracts due to inadequate capacity and regulations. The purpose of this study is to determine the sharia of the contract in cooperatives, Study at KPRI UB. This research uses a qualitative method of case studies. The result of this research is that the Savings and Loans Unit (Unit Simpan Pinjam) of KPRI UB has savings products with Mudharabah and Wadiah contracts, as well as financing or loan products with Ijarah, Murabahah, Qardh, and Musyarakah Mutanaqisah contracts. The Savings and Loans Unit (Unit Simpan Pinjam) of KPRI UB has the meaning, requirements, and mechanism of the contract that is in accordance with sharia provisions, but in its application there are still procedures that are not applied.